2014
DOI: 10.1093/mp/ssu066
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Target Genes and Transcription Factors Implicated in Translation-Dependent Retrograde Signaling in Arabidopsis

Abstract: Changes in organellar gene expression (OGE) trigger retrograde signaling. The molecular dissection of OGE-dependent retrograde signaling based on analyses of mutants with altered OGE is complicated by compensatory responses that mask the primary signaling defect and by secondary effects that influence other retrograde signaling pathways. Therefore, to identify the earliest effects of altered OGE on nuclear transcript accumulation, we have induced OGE defects in adult plants by ethanol-dependent repression of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 80 publications
(102 reference statements)
1
11
1
Order By: Relevance
“…It has been noted before that light and chloroplast signaling pathways converge at some point (Ruckle et al, 2007;Leister et al, 2014;Martín et al, 2016). In agreement with this, we have identified PIF-related ciselements in the promoters of pp7l-deregulated genes (Fig.…”
Section: The Role Of Pp7l In Chloroplast Development Is Not Mediated supporting
confidence: 91%
“…It has been noted before that light and chloroplast signaling pathways converge at some point (Ruckle et al, 2007;Leister et al, 2014;Martín et al, 2016). In agreement with this, we have identified PIF-related ciselements in the promoters of pp7l-deregulated genes (Fig.…”
Section: The Role Of Pp7l In Chloroplast Development Is Not Mediated supporting
confidence: 91%
“…Interestingly, it was recently shown that phototropins are required to maintain robust circadian oscillations in photosystem II efficiency under constant blue light (Litthauer et al ). Furthermore, we previously suggested that early OGE‐dependent signaling (triggered by an impairment of PRORS1), and temperature‐acclimation and light‐signaling pathways might target the same transcription factors (Leister et al ). The mutants that are defective in mTERF proteins – namely mterf9 , mda1 , rug2‐1 and s oldat10 plants – also flower earlier than WT (reviewed in Kleine and Leister ) provides another link between mTERF/OGE‐ and light‐signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Affymetrix ATH1-121501 data were from the following sources: Gene Expression Omnibus https://www.ncbi.nlm.nih.gov/geo/, AA 3 hours (in figures labelled as experiment 1), GSE57140 (Ivanova et al, 2014); AA and H 2 O 2 , 3 hour treatments (in figures labelled as experiment 2), GSE41136 (Ng et al 2013); MV 3 hours, GSE41963 (Sharma et al, 2013); mterf6-1, GSE75824 (Leister and Kleine 2016); prors1-2, GSE54573 (Leister et al, 2014); H 2 O 2 30 min, GSE43551 (Gutiérrez et al, 2014); high light 1 hour (in figures labelled as experiment 1), GSE46107 (Van Aken et al, 2013); high light 30 min in cell culture, GSE22671 (González-Pérez et al, 2011); high light 3 hours (in figures labelled as experiment 2), GSE7743 (Kleine et al, 2007); oligomycin 1 and 4 hours, GSE38965 (Geisler et al, 2012); norflurazon – 5 day-old seedlings grown on plates with norflurazon, GSE12887 (Koussevitzky et al, 2007); msh1 recA3 double mutant, GSE19603 (Shedge et al, 2010). AtGenExpress oxidative time series, MV 12 and 24 hours, http://www.arabidopsis.org/servlets/TairObject?type=expressionset&id=1007966941.…”
Section: Methodsmentioning
confidence: 99%